Selective blockage of Serratia marcescens ShlA by nickel inhibits the pore‐forming toxin‐mediated phenotypes in eukaryotic cells. (31st May 2019) - Lazzaro, Martina; Krapf, Darío; García Véscovi, Eleonora
Abstract: Serratia marcescens is an opportunistic pathogen with increasing incidence in clinical settings. This is mainly attributed to the timely expression of a wide diversity of virulence factors and intrinsic and acquired resistance to antibiotics, including β‐lactams, aminoglycosides, quinolones, and polypeptides. For these reasons, S. marcescens has been recently categorised by the World Health Organization as one priority to strengthen efforts directed to develop new antibacterial agents. Therefore, it becomes critical to understand the underlying mechanisms that allow Serratia to succeed within the host. S. marcescens ShlA pore‐forming toxin mediates phenotypes that alter homeostatic and signal transduction pathways of host cells. It has been previously demonstrated that ShlA provokes cytotoxicity, haemolysis and autophagy and also directs Serratia egress and dissemination from invaded nonphagocytic cells. However, molecular details of ShlA mechanism of action are still not fully elucidated. In this work, we demonstrate that Ni 2+ selectively and reversibly blocks ShlA action, turning wild‐type S. marcescens into a shlA mutant strain phenocopy. Combined use of Ni 2+ and calcium chelators allow to discern ShlA‐triggered phenotypes that require intracellular calcium mobilisation and reveal ShlA function as a calcium channel, providing new insights into ShlA mode of action on target cells.